Involvement of Sphingolipid Metabolism Enzymes in Resveratrol-Mediated Cytotoxicity in Philadelphia-Positive Acute Lymphoblastic Leukemia - Oguz, Osman; Adan, Aysun (Routledge Journals, Taylor & Francis Ltd, 2021)
Targeting the key enzymes of sphingolipid metabolism including serine palmitoyltransferase (SPT), sphingosine kinase (SK) and glucosylceramide synthase (GCS) has a therapeutic importance. However, sphingolipid metabolism-mediated anti-leukemic actions of resveratrol in Philadelphia-positive acute lymphoblastic leukemia (Ph + ALL) remain unknown. Therefore, we explored potential mechanisms behind resveratrol-mediated cytotoxicity in SD1 and SUP-B15 Ph + ALL cells in the context of sphingolipid metabolism and apoptosis induction. The anti-proliferative and apoptotic effects of resveratrol alone and in combination with SPT inhibitor (myriocin), SK inhibitor (SKI II), GCS inhibitor (PDMP) were determined by MTT cell proliferation assay and flow cytometry, respectively. The effects of resveratrol on PARP cleavage, SPT, SK and GCS protein levels were investigated by Western blot. Resveratrol inhibited proliferation and triggered apoptosis via PARP activation and externalization of phosphatidylserine (PS). Resveratrol increased the expression of SPT whereas it downregulated SK and GCS. Resveratrol's combinations with SKI II and PDMP intensified its anti-leukemic activity by increasing the relocalization of PS while its combination with myriocin suppressed apoptosis. Therefore, resveratrol inhibited cell proliferation and induced apoptosis through modulating SK, GCS and SPT expression, which may be considered as novel biomarkers of resveratrol-induced cytotoxicity in Ph + ALL.
Adan, Aysun/0000-0002-3747-8580;